2019
DOI: 10.2147/tcrm.s160248
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to early treatment of idiopathic pulmonary fibrosis: current perspectives

Abstract: Idiopathic pulmonary fibrosis is a progressive and fatal fibrotic lung disease which has seen new opportunity for drug treatment in the last several years with the approval of nintedanib and pirfenidone, two antifibrotic agents aimed at slowing decline in lung function as defined by FVC on pulmonary function testing. Despite these promising effects, delays in drug initiation have been reported undermining the premise that earlier drug initiation may sustain lung function and prolong survival. This review explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 73 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…2 With an appearance of characteristic radiography, IPF mostly appeared in the pathological lesion of common interstitial pneumonia. 2 With an appearance of characteristic radiography, IPF mostly appeared in the pathological lesion of common interstitial pneumonia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 With an appearance of characteristic radiography, IPF mostly appeared in the pathological lesion of common interstitial pneumonia. 2 With an appearance of characteristic radiography, IPF mostly appeared in the pathological lesion of common interstitial pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic pulmonary fibrosis (IPF), a progressive and chronic fibrosing interstitial pneumonia without a clear cause, 1 may worsen lung function or lead to death. 2 With an appearance of characteristic radiography, IPF mostly appeared in the pathological lesion of common interstitial pneumonia. 3 With a 2 to 5 years of survival time from diagnosis, IPF mainly occurs among elderly adults.…”
Section: Introductionmentioning
confidence: 99%
“… 56 , 57 Since spirometric endpoints can function as determinants in initiating antifibrotic therapy, the presence of emphysema potentially is problematic since it can affect FVC in a manner dissimilar to fibrosis. 58 A single center retrospective study of 45 CPFE patients detected no significant difference in the efficacy of either pirfenidone or nintedanib on measured variables including mortality. 59 Randomized control trials, meta-analysis, and an observation study of pirfenidone in IPF have observed improved progression-free survival and reduced all-cause mortality.…”
Section: Discussionmentioning
confidence: 97%
“…Since then, several studies have confirmed the clinical efficacy of these drugs, including one recent observational study demonstrating that patients may have lower mortality and hospitalization rates when compared to those not on treatment [ 8 10 ]. Despite these benefits and the lack of other effective treatment options, there are still concerns about anti-fibrotics, including their cost (more than $100,000 per year in the United States), which may add to the economic burden of patients with IPF [ 11 ].…”
Section: Introductionmentioning
confidence: 99%